Análise do desempenho dos sistemas de abastecimento de água públicos e privados de Mato Grosso - Turini, Larissa Rodrigues (2021)
The water supply service is one of the four axes that make up the basic sanitation infrastructure, with the purpose of providing drinking water to meet the demands of the population. Twenty years ago, there was a change in the provision of this service in the state of Mato Grosso, which was centralized by the Mato Grosso State Sanitation Company (SANEMAT) and which started to be decentralized in the transfer to the municipalities. Therefore, the relevance of this study is justified by the panorama of this new format, guided by the hypothesis of a current inefficient management by the municipalities. Thus, the main objective of this work is the performance analysis of water supply systems (SAA) in 120 municipalities in the state of Mato Grosso, using unpublished data, obtained in the years 2015 to 2017 through the Municipal Basic Sanitation Plans (PMSB). It should be noted that the selected municipalities have a population of less than 50,000 inhabitants and represent 94% of the state's municipalities and 85% of Brazilian cities. The methodology was presented in three stages: in the first, 27 quantitative variables were selected using data and information available in the 120 PMSB’s. The selection of these variables was defined based on literature references and assistance from specialists in the area, covering technical and operational, organizational and economic aspects; in the second, the statistical analysis of the T test was applied, with the same variables as in the previous phase, in order to verify if there are differences between the provision of public versus private service, with a confidence level of 5%. Finally, they were considered control variables and regression methods for the analysis of outcome variables coverage, loss, default rate and intermittency, using the ordinary least square method (OLS) and propensity score matching (PSM), in order to verify the association between these outcome variables and the provider's property, private or public. The results of the descriptive analysis reveal a precarious situation of SAA in the 120 municipalities in the state of Mato Grosso, in need of investment and improvement in governance. The application of Test T and regressions showed that the private sector does not stand out in relation to the public.